2014
DOI: 10.3390/v6010301
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Epstein-Barr Virus Association with Gastric Cancer and Non-Atrophic Gastritis

Abstract: Different lines of evidence support an association between Epstein-Barr virus (EBV) and gastric cancer (GC). The main understood risk factor to develop GC is infection by Helicobacter pylori (H. pylori), which triggers a local inflammatory response critical for progression from gastritis to GC. The role of EBV in early inflammatory gastric lesions has been poorly studied. A recent study proposed a cutoff value of 2000 EBV particles to identify patients with increased chances of infection of the gastric epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 37 publications
2
52
1
1
Order By: Relevance
“…Another study involving 53 Brazilian patients from the State of São Paulo revealed 11.3% positivity, with male predominance (83.3%), median age of 59 years and a higher incidence of lesions in the gastric antrum (41.5%) (41) . Similarly, a prevalence of 9.6% was found in 39 patients from the City of Belém, State of Pará (20) , and another study, also involving a population from Northern Brazil, but including only ten GC patients and six controls without tumor, found that eight patients had EBV DNA in their tumor cells, with no positivity in the control group (22) . There is no data available about the prognostic value of EBV infection in the Brazilian population.…”
Section: Ebv-positive Gc In Brazilmentioning
confidence: 79%
See 1 more Smart Citation
“…Another study involving 53 Brazilian patients from the State of São Paulo revealed 11.3% positivity, with male predominance (83.3%), median age of 59 years and a higher incidence of lesions in the gastric antrum (41.5%) (41) . Similarly, a prevalence of 9.6% was found in 39 patients from the City of Belém, State of Pará (20) , and another study, also involving a population from Northern Brazil, but including only ten GC patients and six controls without tumor, found that eight patients had EBV DNA in their tumor cells, with no positivity in the control group (22) . There is no data available about the prognostic value of EBV infection in the Brazilian population.…”
Section: Ebv-positive Gc In Brazilmentioning
confidence: 79%
“…In healthy individuals, infection of the gastric epithelial cells is rare (20) (21) (22) , and the mechanisms underlying infection of the gastric mucosa by EBV remain unknown. It is assumed that EBV infection is an early event in carcinogenesis, owing to evidence of virus infection in premalignant lesions, such as dysplastic epithelial cells (2) (21) (23) .…”
Section: Epstein-barr Virus In Gastric Cancermentioning
confidence: 99%
“…15 Initially, EBV was found only in lymphocytes infiltrating gastric tumours; later its presence was demonstrated in non-atrophic and non-metaplastic mucosa. 16 Much less is known about EBV in benign upper gastrointestinal diseases. Lymphocytes are only rarely seen in normal (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…At present, nested PCR and quantitative real-time PCR are commonly used Lin et al, 2014;Martinez-Lopez et al, 2014;Sousa et al, 2011). Nucleic acid diagnosis can indicate the existence of a viral genome and provides direct results, with the advantages of high sensitivity, specificity and quantitative monitoring.…”
Section: Discussionmentioning
confidence: 99%